Kesadaran Hukum dan Kepatuhan Hukum: Analisis Faktor yang Mempengaruhi Kesadaran Hukum dan Kepatuhan Hukum Masyarakat - Syamsarina Syamsarina; M. Ibrahim Aziz; Arzam Arzam; Defril Hidayat; Ari Bakti Windi Aji (Jurnal Selat, 2022)
A sense of justice is an abstract human conception of a desired or proper harmony between order and peace. Legal awareness is often associated with legal suitability, legal design, and legal validity. Legal awareness is the perception of value contained in humans about existing laws. Compliance comes from the word obedience and means obedience, obedience, obedience. To obey means to bow, obey, obey. Obedience means submission, and obedience is the state of submission to something or someone. Compliance, therefore, is the condition that the general public follows the rules of the game (the law). A society's legal culture also recognizes that our society, in its legal consciousness, has laws as rules of the game for living together and as a basis for solving problems arising from the risks of living together. However, from a material point of view, it is very difficult to build a legal culture in this country. This situation is affected by several factors, including: 1) legal factors; 2) law enforcement factors; 3) institutions and facilities; 4) community factors; and 5) cultural factors.